A study on the escape rate of Northeast Atlantic cod (Gadus morhua) and haddock (Melanogrammus aeglefinus) under the fishing line with two different ground ropes in the Barents Sea bottom trawl fishery and the influence of some biotic and abiotic factors on the efficiency during bottom trawling - Brinkhof, Jesse (UiT The Arctic University of Norway, 2015)
The aim of this study was to investigate the escapement under the fishing line for cod (Gadus morhua) and haddock (Melanogrammus aeglefinus) with the conventional rock-hopper gear and a new type of gear termed semicircular spreading gear (SCSG). The trials were conducted during November 2014 and February 2015 in the Barents Sea under varying environmental conditions. In order to catch the escapees a retainer bag was attached to the fishing line of the trawl. Multi model averaging was applied for calculating the efficiency, i.e. escapement rate for all length groups. A highly significant difference in the rate of escapement between the two types of ground-gears was found. Summarized for all length groups above 65 cm, 14% of the cod escaped under the fishing line of the rock-hopper gear, and 5% under the SCSG during the trials in November 2014. This resulted in an efficiency improvement of 11%, and escapement reduction of 67%. In February 2015 the escapement was 5% for the rock-hopper, and 2% for the SCSG, resulting in an efficiency improvement of 3%, and an escapement reduction of 57%. The overall improvement of efficiency for cod is thus 8%, and a reduction in escapement of 63%. The escapement of haddock for all lengths above 62 cm was estimated to 7% for the rock-hopper gear, and 1% for the SCSG, implying an efficiency improvement of 6%, and an escapement reduction of 85%. Based on the present data no correlation was found between the rate of escapement and fish density, ambient light intensity, nor artificial light. However, a positive correlation was obtained between temperature and the escapement rate for some length groups. Over the recent years the tendency in the bottom trawl fisheries has been increasing the trawl dimension in order to increase efficiency, with subsequent increase in fuel consumption and emission, as well as possibly increased negative bottom impact. The demonstrated improvement of the SCSG compared to the conventional rock-hopper gear entails multiple advantages such as increased ...